The impact of the global financial crisis on the economy of Sierra Leone: A report for UNDP Freetown and the Ministry of Finance and Economic Development, Republic of Sierra Leone - John Weeks (International Policy Centre for Inclusive Growth (IPC-IG), 2009)
[Global crisis and poverty prevention] Most recent statistics indicate that the global financial crisis will cause a fall in export earnings in Sierra Leone of approximately fifteen percent in 2009 compared to 2008. A regression-based model estimates that this decline in exports earnings could result in a fall in national income of almost ten percent. Based on the income distribution in the 2003 household survey, a ten percent decline in national income would increase poverty by twelve percent of the population, or about 600,000 people. A fiscal stimulus of two percent of GDP could stabilise the economy at the level of 2008, preventing this disastrous increase in poverty. A stimulus package consisting of employment intensive public works programmes could be designed to return the economy to its pre-shock level with a reduction in poverty. (...)
Keywords: 330; Finanzmarktkrise; Makroökonomischer Einfluss; Sierra Leone